THE CORRELATION BETWEEN DEMOCRATIC PARENTING AND 4-5 YEAR-OLD CHILDREN’S AUTONOMY IN GONILAN VILLAGE - Fatimah Suha Nur Hidayah; Ruli Hafidah; Nurul Kusuma Dewi (Early Childhood Education and Development Journal, 2020)
Planting character values needs to be given from an early age. One of the character values that needs to be instilled early is independence.The role and parent's support is needed to build an independent child character. Parenting is one of the factors that influence children's independence. The purpose of this study was to find out whether there was a relationship between democratic parenting and disciplines of children aged 4-5 years in Gonilan Village. This study uses quantitative approaches with correlation research type. This research was conducted on January 2019 by using a sample of 69 children and parents of children aged 4-5 years in Gonilan Village. Retrieving data from this study uses questionnaires that distributed to the parents. The results of the hypothesis test of the Spearman Rho correlation indicate that the significance value is 0,000 <0.05 which means the hypothesis is accepted, there is a relationship between democratic parenting with the independence of children aged 4-5 years in Gonilan Village. The results of the correlation coefficient are 0.998 using the Spearman Rho hypothesis test, which means the higher the democratic parenting style of parents, the higher the child's independence.